Preparation method of high-fluidity polyamide composite material with non-whitening surface of automobile door frame trim
By grafting hyperbranched polyamide on the surface of molecular sieves, the compatibility between glass fiber and polyamide and the adsorption efficiency of oligomers are improved, which solves the problems of reduced fluidity and floating fiber phenomenon of polyamide materials, and achieves high fluidity and excellent Polyamide composite exterior.
Patent Information
- Application Number
- CN202411018041.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-07-29
AI Technical Summary
The fluidity of the polyamide material decreases significantly after adding glass fiber to polyamide, and the compatibility of glass fiber with polyamide is poor. The finished product is prone to floating fiber phenomenon, and the oligomer precipitates white substances at the welding wire affects the aesthetics.
In-situ grafting of hyperbranched polyamide on the surface of the molecular sieve improves the adsorption efficiency of polyamide oligomers, and improves the compatibility of glass fiber and polyamide through hydrogen bonding interactions between hyperbranched polyamide and glass fiber.
Effectively reduce the viscosity of polyamide composite materials, improve liquidity, avoid floating fiber phenomenon, and solve the problem of white polymer analysis, improve the appearance and anti -impact performance of the finished product.
Smart Images

Figure BDA0004966325670000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a method for preparing a high-fluidity polyamide composite material whose surface does not turn white. Background Art
[0002] Polyamide is a polymer engineering plastic with multiple repeating polyamide groups on the main chain of the molecule. It has excellent mechanical properties, chemical resistance, heat resistance, easy processing and other properties. It is widely used in automotive functional structural parts and interior and exterior decoration materials. In order to improve the performance of polyamide materials, reinforcing materials such as glass fiber are often added thereto. However, the fluidity of polyamide materials decreases significantly after the addition of glass fiber, and the compatibility of glass fiber and polyamide is poor, and the finished product is prone to floating fiber phenomenon. In addition, the parts of automobile door and window frame trims are relatively large, and each part has 20-30 gates. Weld lines are prone to appear between the two gates, and polyamide materials contain unreacted oligomers, which are prone to precipitate white precipitates at and around the weld line, affecting the appearance. Therefore, it is urgent to solve the above problems and provide a high-fluidity polyamide composite material with a non-white surface for automobile door frame trims. Summary of the invention
[0003] The object of the present invention is to provide a method for preparing a high-fluidity polyamide composite material whose surface of an automobile door frame trim strip does not turn white. A hyperbranched polyamide is grafted in situ on the surface of a molecular sieve to obtain a hyperbranched polyamide grafted modified molecular sieve, which can adsorb oligomers and solve the problem of oligomer precipitation and whitening. The hyperbranched polyamide is grafted on the surface of the molecular sieve to improve the adsorption efficiency of polyamide oligomers. The hyperbranched polyamide grafted modified molecular sieve and the hyperbranched polyamide added in the preparation process of the polyamide composite material work together to effectively reduce the viscosity of the polyamide composite material and improve the fluidity of the polyamide composite material. At the same time, the compatibility of glass fiber and polyamide is improved, so that the surface of the finished product does not float fiber and has a good appearance. The polyamide composite material prepared by the present invention has excellent impact resistance.
[0004] The technical problem to be solved by the present invention is that the fluidity of polyamide material decreases significantly after adding glass fiber, and the compatibility of glass fiber and polyamide is poor, and the finished product is prone to floating fiber phenomenon. In addition, the oligomers contained in polyamide are prone to precipitate white precipitates at the weld line and its surroundings, which affects the appearance.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A method for preparing a high-fluidity polyamide composite material whose surface does not turn white for an automobile door frame trim comprises the following steps:
[0007] A1, dispersing silicon source, aluminum source, organic template and alkali source in deionized water, mixing them evenly and placing them in a crystallization kettle for hydrothermal reaction to obtain a molecular sieve;
[0008] In the above preparation process, the pores of the prepared molecular sieve contain organic templates which are not removed.
[0009] Furthermore, in step A1, the silicon source is at least one of silica sol, silicon dioxide, water glass and tetraethyl orthosilicate.
[0010] Furthermore, in step A1, the aluminum source is at least one of aluminum nitrate, aluminum sulfate, aluminum isopropoxide, pseudo-boehmite, and aluminum chloride.
[0011] Furthermore, in step A1, the organic template is at least one of tetramethylammonium hydroxide, tetrapropylammonium hydroxide, ethylenediamine, and hexamethylenediamine.
[0012] Furthermore, in step A1, the temperature of the hydrothermal reaction is 170-240° C., and the time is 26-72 h.
[0013] Furthermore, in step A1, the mass ratio of the silicon source, the aluminum source, the organic template and the alkali source is (5-5.3): (0.3-0.7): (2.1-4.3): (0.25-0.65).
[0014] A2, using an aminosilane coupling agent to graft-modify the surface of the molecular sieve to obtain an amino-modified molecular sieve;
[0015] In the above preparation process, an aminosilane coupling agent containing two amine groups is used to graft-modify the surface of the molecular sieve, so that the surface of the molecular sieve contains amine groups.
[0016] Furthermore, in step A2, the aminosilane coupling agent is at least one of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltriethoxysilane and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane.
[0017] Furthermore, in step A2, the mass ratio of the aminosilane coupling agent to the molecular sieve is 1-3:1.
[0018] Furthermore, in step A2, the temperature during the grafting modification process is 70-90° C. and the time is 12-24 hours.
[0019] A3, putting the amino-modified molecular sieve and diethylenetriamine into a solvent, stirring evenly, adding succinic anhydride to react, and performing microwave digestion after the reaction to obtain a hyperbranched polyamide grafted modified molecular sieve;
[0020] In the above-mentioned preparation process, the amino-modified molecular sieve is reacted with diethylenetriamine and succinic anhydride, thereby in-situ grafting hyperbranched polyamide on the molecular sieve surface, and then the organic template in the molecular sieve pores is eliminated by microwave digestion to obtain a hyperbranched polyamide grafted modified molecular sieve. The present invention grafts the hyperbranched polyamide on the molecular sieve surface, thereby improving the compatibility of the molecular sieve with the polyamide resin. The hyperbranched polyamide grafted modified molecular sieve prepared by the present invention can be used as an adsorbent for polyamide oligomers, can adsorb polyamide oligomers, and solves the problem of oligomer precipitation and whitening. In addition, the present invention grafts the hyperbranched polyamide on the molecular sieve surface, which can improve the adsorption efficiency of polyamide oligomers.
[0021] The hyperbranched polyamide end groups grafted onto the surface of the molecular sieve of the present invention contain a large number of active amino groups, which interact with the hydroxyl groups on the surface of the glass fiber through hydrogen bonds, thereby bridging the molecular sieve and the glass fiber, thereby improving the impact resistance of the composite material. In addition, the hyperbranched polyamide grafted onto the surface of the molecular sieve has a cavity structure, which can improve the impact resistance. At the same time, an aminosilane coupling agent containing two amine groups is used in the process of preparing the hyperbranched polyamide to react with diethylenetriamine and succinic anhydride, so that the density of the hyperbranched polyamide is higher, thereby further improving the impact resistance of the composite material.
[0022] Furthermore, in step A3, the usage ratio of the amino-modified molecular sieve, diethylenetriamine, succinic anhydride and solvent is (2-2.5): (3.3-3.7): (10.6-12.3): (170-200) mL.
[0023] Furthermore, in step A3, the reaction temperature is 120-130° C. and the reaction time is 7-9 h.
[0024] Furthermore, in step A3, the microwave digestion treatment temperature is 130-180° C. and the time is 22-28 min.
[0025] A4. Add polyamide resin, hyperbranched polyamide, hyperbranched polyamide grafted modified molecular sieve and additives into a high-speed blender for premixing to obtain a premix; feed the premix into a twin-screw extruder from a main feeding port, feed the glass fiber into the twin-screw extruder from a side feeding port, and melt-extrude and granulate to obtain the product.
[0026] Furthermore, in step A4, the polyamide resin is at least one of PA6 or PA66.
[0027] Furthermore, in step A4, the auxiliary agent is at least one of a lubricant, an antibacterial agent, and an antioxidant.
[0028] Furthermore, in step A4, the mass ratio of polyamide resin, glass fiber, hyperbranched polyamide, hyperbranched polyamide grafted modified molecular sieve and additive is (55-70):(20-30):(1-3):(0.5-3):(0.1-4).
[0029] Furthermore, in step A4, the temperature of the twin-screw extruder is 245-280° C., and the screw speed is 250-400 rpm.
[0030] Furthermore, in step A4, the length of the glass fiber is 2-5 mm and the diameter is 7-12 μm.
[0031] The hyperbranched polyamide grafted modified molecular sieve prepared by the present invention and the hyperbranched polyamide added in the preparation process of the polyamide composite material work together to effectively reduce the viscosity of the polyamide composite material and improve the fluidity of the polyamide composite material. At the same time, the hyperbranched polyamide end group contains a large number of active amino groups that interact with the hydroxyl groups on the surface of the glass fiber through hydrogen bonds, thereby improving the compatibility of the glass fiber and the polyamide, so that the surface of the finished product does not have floating fibers and has a good appearance.
[0032] Beneficial effects of the present invention:
[0033] (1) In the technical solution of the present invention, an amino-modified molecular sieve is reacted with diethylenetriamine and succinic anhydride, thereby in-situ grafting a hyperbranched polyamide on the surface of the molecular sieve, and then the organic template in the molecular sieve pores is eliminated by microwave digestion to obtain a hyperbranched polyamide grafted modified molecular sieve. The present invention grafts the hyperbranched polyamide on the surface of the molecular sieve, thereby improving the compatibility of the molecular sieve with the polyamide resin. The hyperbranched polyamide grafted modified molecular sieve prepared by the present invention can be used as an adsorbent for polyamide oligomers, and can adsorb polyamide oligomers, thereby solving the problem of oligomer precipitation and whitening. In addition, the present invention grafts the hyperbranched polyamide on the surface of the molecular sieve, thereby improving the adsorption efficiency of the polyamide oligomers.
[0034] (2) In the technical solution of the present invention, the end groups of the hyperbranched polyamide grafted on the surface of the molecular sieve contain a large number of active amino groups that interact with the hydroxyl groups on the surface of the glass fiber through hydrogen bonds, thereby bridging the molecular sieve and the glass fiber, thereby improving the impact strength of the composite material. In addition, the hyperbranched polyamide grafted on the surface of the molecular sieve has a cavity structure, which can improve the impact resistance. At the same time, an aminosilane coupling agent containing two amine groups is used in the preparation process of the hyperbranched polyamide to react with diethylenetriamine and succinic anhydride, so that the density of the hyperbranched polyamide is higher, thereby further improving the impact resistance of the composite material.
[0035] (3) In the technical solution of the present invention, the hyperbranched polyamide grafted modified molecular sieve and the hyperbranched polyamide added in the preparation process of the polyamide composite material work together to effectively reduce the viscosity of the polyamide composite material and improve the fluidity of the polyamide composite material. At the same time, the end groups of the hyperbranched polyamide contain a large number of active amino groups that interact with the hydroxyl groups on the surface of the glass fiber through hydrogen bonds, thereby improving the compatibility of the glass fiber and the polyamide, so that the surface of the finished product does not float and has a good appearance. DETAILED DESCRIPTION
[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] A method for preparing a high-fluidity polyamide composite material whose surface does not turn white for an automobile door frame trim comprises the following steps:
[0039] A1. Disperse 30 g of aluminum nitrate, 210 g of tetramethylammonium hydroxide and 25 g of sodium hydroxide in 500 mL of deionized water, stir for 2 h, then add 500 g of tetraethyl orthosilicate, stir for 24 h, then transfer to a crystallization kettle, react at 170 ° C for 26 h, take out the reaction product after the reaction is completed, filter, wash and dry to obtain a molecular sieve;
[0040] A2, 100g N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane was dissolved in 3L anhydrous ethanol, and 100g molecular sieve was added, and stirred evenly, and refluxed at 70°C for 12h under the protection of nitrogen, and filtered, washed and dried to obtain amino-modified molecular sieve;
[0041] A3, put 100g amino-modified molecular sieve and 165g diethylenetriamine into 8.5LN,N-dimethylformamide, stir evenly, add 530g succinic anhydride, react at 120°C for 7h, wash and dry, put into a microwave digestion tank, add sulfuric acid and hydrogen peroxide in a mass ratio of 3:1, microwave digestion at 130°C for 22min, filter, wash and dry to obtain hyperbranched polyamide grafted modified molecular sieve;
[0042] A4, 550g PA6, 10g hyperbranched polyamide, 5g hyperbranched polyamide grafted modified molecular sieve and 10g pentaerythritol stearate, added to a high-speed blender for premixing to obtain a premix; the premix was fed into a twin-screw extruder from a main feeding port, 200g glass fiber was fed into the twin-screw extruder from a side feeding port, melt-extruded and granulated, the extrusion temperatures were set to: 245°C, 260°C, 270°C, 280°C, 280°C, 280°C, 270°C, 260°C, and the main screw speed was 250rpm, to obtain.
[0043] Example 2
[0044] A method for preparing a high-fluidity polyamide composite material whose surface does not turn white for an automobile door frame trim comprises the following steps:
[0045] A1. Disperse 40 g of aluminum isopropoxide, 280 g of tetrapropylammonium hydroxide and 34 g of sodium hydroxide in 500 mL of deionized water, stir for 2 h, then add 510 g of ethyl orthosilicate, stir for 24 h, then transfer to a crystallization kettle, react at 180 ° C for 30 h, take out the reaction product after the reaction is completed, filter, wash and dry to obtain a molecular sieve;
[0046] A2, 145g N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane was dissolved in 3L anhydrous ethanol, and 100g molecular sieve was added, stirred evenly, and refluxed at 80°C for 16h under the protection of nitrogen, filtered, washed and dried to obtain amino-modified molecular sieve;
[0047] A3, put 112g of amino-modified molecular sieve and 173g of diethylenetriamine into 9LN,N-dimethylformamide, stir evenly, add 562g of succinic anhydride, react at 120°C for 8h, wash and dry, put into a microwave digestion tank, add a digestion solution of sulfuric acid and hydrogen peroxide in a mass ratio of 3:1, microwave digestion treatment at 150°C for 24min, filter, wash and dry to obtain a hyperbranched polyamide grafted modified molecular sieve;
[0048] A4, 600g PA6, 16g hyperbranched polyamide, 11g hyperbranched polyamide grafted modified molecular sieve and 18g pentaerythritol stearate, added to a high-speed blender for premixing to obtain a premix; the premix was fed into a twin-screw extruder from a main feeding port, 280g of glass fiber was fed into the twin-screw extruder from a side feeding port, melt-extruded and granulated, the extrusion temperatures were set to: 245°C, 260°C, 270°C, 280°C, 280°C, 280°C, 270°C, 260°C, and the main screw speed was 300rpm, to obtain.
[0049] Example 3
[0050] A method for preparing a high-fluidity polyamide composite material whose surface does not turn white for an automobile door frame trim comprises the following steps:
[0051] A1. Disperse 50 g of aluminum chloride, 310 g of tetrapropylammonium hydroxide and 44 g of sodium hydroxide in 500 mL of deionized water, stir for 2 h, then add 516 g of ethyl orthosilicate, stir for 24 h, then transfer to a crystallization kettle, react at 200 ° C for 48 h, take out the reaction product after the reaction is completed, filter, wash and dry to obtain a molecular sieve;
[0052] A2, 160g N-β-(aminoethyl)-γ-aminopropyltriethoxysilane was dissolved in 3L anhydrous ethanol, and 100g molecular sieve was added, and stirred evenly, and refluxed at 80°C for 18h under the protection of nitrogen, and filtered, washed and dried to obtain amino-modified molecular sieve;
[0053] A3, put 114g amino-modified molecular sieve and 175g diethylenetriamine into 9.5LN,N-dimethylformamide, stir evenly, add 594g succinic anhydride, react at 130°C for 8h, wash and dry, put into a microwave digestion tank, add sulfuric acid and hydrogen peroxide in a mass ratio of 3:1, microwave digestion treatment at 150°C for 25min, filter, wash and dry to obtain hyperbranched polyamide grafted modified molecular sieve;
[0054] A4, 620g PA6, 20g hyperbranched polyamide, 18g hyperbranched polyamide grafted modified molecular sieve and 18g pentaerythritol stearate, added to a high-speed blender for premixing to obtain a premix; the premix was fed into a twin-screw extruder from the main feeding port, 280g glass fiber was fed into the twin-screw extruder from the side feeding port, melt extrusion granulation, the extrusion temperature was set to: 245°C, 260°C, 270°C, 280°C, 280°C, 280°C, 270°C, 260°C, the main screw speed was 350rpm,
[0055] Example 4
[0056] A method for preparing a high-fluidity polyamide composite material whose surface does not turn white for an automobile door frame trim comprises the following steps:
[0057] A1. Disperse 60 g of aluminum sulfate, 370 g of tetramethylammonium hydroxide and 52 g of sodium hydroxide in 500 mL of deionized water, stir for 2 h, then add 520 g of ethyl orthosilicate, stir for 24 h, then transfer to a crystallization kettle, react at 210 ° C for 56 h, take out the reaction product after the reaction is completed, filter, wash and dry to obtain a molecular sieve;
[0058] A2, 260g N-β-(aminoethyl)-γ-aminopropyltriethoxysilane was dissolved in 3L anhydrous ethanol, and 100g molecular sieve was added, and stirred evenly, and refluxed at 85°C for 12h under the protection of nitrogen, and filtered, washed and dried to obtain amino-modified molecular sieve;
[0059] A3, put 116g of amino-modified molecular sieve and 178g of diethylenetriamine into 10LN,N-dimethylformamide, stir evenly, add 600g of succinic anhydride, react at 130°C for 9h, wash and dry, put into a microwave digestion tank, add a digestion solution of sulfuric acid and hydrogen peroxide in a mass ratio of 3:1, microwave digestion treatment at 170°C for 22min, filter, wash and dry to obtain a hyperbranched polyamide grafted modified molecular sieve;
[0060] A4, 700g PA6, 30g hyperbranched polyamide, 10g hyperbranched polyamide grafted modified molecular sieve and 8g pentaerythritol stearate, added to a high-speed blender for premixing to obtain a premix; the premix was fed into a twin-screw extruder from a main feeding port, 200g glass fiber was fed into the twin-screw extruder from a side feeding port, melt extrusion granulation, the extrusion temperatures were set to: 245°C, 260°C, 270°C, 280°C, 280°C, 280°C, 270°C, 260°C, the main screw speed was 350rpm, to obtain.
[0061] Example 5
[0062] A method for preparing a high-fluidity polyamide composite material whose surface does not turn white for an automobile door frame trim comprises the following steps:
[0063] A1. Disperse 70g of aluminum nitrate, 430g of tetramethylammonium hydroxide and 65g of sodium hydroxide in 500mL of deionized water, stir for 2h, then add 530g of ethyl orthosilicate, stir for 24h, then transfer to a crystallization kettle, react at 240°C for 2h, take out the reaction product after the reaction is completed, filter, wash and dry to obtain a molecular sieve;
[0064] A2, 300g N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane was dissolved in 3L anhydrous ethanol, and 100g molecular sieve was added, stirred evenly, and refluxed at 90°C for 12h under the protection of nitrogen, filtered, washed and dried to obtain amino-modified molecular sieve;
[0065] A3, put 125g of amino-modified molecular sieve and 185g of diethylenetriamine into 10LN,N-dimethylformamide, stir evenly, add 615g of succinic anhydride, react at 130°C for 9h, wash and dry, put into a microwave digestion tank, add sulfuric acid and hydrogen peroxide in a mass ratio of 3:1, microwave digestion treatment at 180°C for 28min, filter, wash and dry to obtain hyperbranched polyamide grafted modified molecular sieve;
[0066] A4, 700g PA6, 10g hyperbranched polyamide, 30g hyperbranched polyamide grafted modified molecular sieve and 18g pentaerythritol stearate, added to a high-speed blender for premixing to obtain a premix; the premix was fed into a twin-screw extruder from a main feeding port, 250g of glass fiber was fed into the twin-screw extruder from a side feeding port, melt-extruded and granulated, the extrusion temperatures were set to: 245°C, 260°C, 270°C, 280°C, 280°C, 280°C, 270°C, 260°C, and the main screw speed was 400rpm, to obtain.
[0067] Comparative Example 1
[0068] Compared with Example 3, the aminosilane coupling agent in Comparative Example 1 is 3-aminopropyltriethoxysilane, and the other steps and raw materials are the same as those in Example 3.
[0069] Comparative Example 2
[0070] Compared with Example 3, in Comparative Example 2, the outer surface of the amino-modified molecular sieve is not in-situ grafted with hyperbranched polyamide, and the other steps and raw materials are the same as those in Example 3.
[0071] Comparative Example 3
[0072] Compared with Example 3, in Comparative Example 3, no hyperbranched polyamide was added in step A4, and other steps and raw materials were the same as those in Example 3.
[0073] Performance Testing
[0074] The polyamide composite materials prepared in Examples 1-5 and Comparative Examples 1-3 were tested for their properties. The results are shown in Tables 1 and 2.
[0075] (1) Tensile strength: According to ISO 527 method, tensile speed 5 mm / min.
[0076] (2) Flexural strength: According to ISO 178 method, test speed 2 mm / min.
[0077] (3) Notched impact strength: tested according to ISO 179 method at room temperature 23°C.
[0078] (4) Melt index: according to ISO 1133 method, the test conditions are 280℃, 2.16kg.
[0079] (5) Whitening: A rectangular spline was molded by two-end point pouring method, with the specific size being the UL94 requirement (125 mm × 13 mm × 0.8 mm). The two melts in two directions were allowed to merge in the middle to form a weld line. The whitening around the weld line was visually observed. At the same time, a rectangular spline was molded by one-end point pouring method, with the specific size being the UL94 requirement (125 mm × 13 mm × 1.6 mm). The melt in one direction was allowed to fill the spline cavity. The whitening at the far end of the spline was visually observed.
[0080] (6) Weld line appearance evaluation: A dumbbell-shaped tensile specimen was injected using the two-end point pouring method. The specific dimensions were as required by ISO527 (125 mm × 10 mm × 4 mm). Two melts in different directions were allowed to merge in the middle to form a weld line. The weld line was observed with a magnifying glass. The weld line was then rated based on the depth of the weld line and the color difference with the non-weld line position. The score was 1-6. The higher the score, the less obvious the weld line was. The lower the score, the more obvious the weld line was and the wider it was. A score of 6 means that the weld line is difficult to be observed with the naked eye.
[0081] (7) Surface quality: judged based on visual appearance.
[0082] Table 1
[0083]
[0084] It can be seen from the data in Table 1 that the polyamide composite material prepared by the present invention has excellent mechanical properties and good fluidity. It can be seen from the data of Comparative Example 3 and Comparative Example 1 that since there is only one amino group on the aminosilane coupling agent, the density of the hyperbranched polyamide in the molecular sieve surface medium is reduced, resulting in a decrease in the impact resistance of the composite material. It can be seen from the data of Comparative Example 3 and Comparative Example 2 that since the hyperbranched polyamide is not in-situ grafted on the outer surface of the amino-modified molecular sieve, the compatibility of the molecular sieve and the polyamide is reduced, which in turn leads to a significant decrease in the mechanical properties of the composite material and a decrease in fluidity. It can be seen from the data of Comparative Example 3 and Comparative Example 3 that the addition of hyperbranched polyamide significantly improves the fluidity of the composite material.
[0085] Table 2
[0086] project Whitening Weld Line Appearance Surface quality Example 1 none 5 Smooth, no floating fibers Example 2 none 6 Smooth, no floating fibers Example 3 none 6 Smooth, no floating fibers Example 4 none 6 Smooth, no floating fibers Example 5 none 5 Smoother, no obvious floating fibers Comparative Example 1 none 5 Smoother, no obvious floating fibers Comparative Example 2 More serious 2 Rough, slightly floating Comparative Example 3 slight 4 Rough, obvious floating fibers
[0087] As can be seen from Table 2, the polyamide composite material prepared by the present invention has a smooth surface, no floating fibers, no obvious weld lines, and no oligomer precipitation whitening phenomenon. It can be seen from the data of Comparative Example 3 and Comparative Example 2 that since the outer surface of the amino-modified molecular sieve is not in-situ grafted with hyperbranched polyamide, the molecular sieve is easy to agglomerate, resulting in a decrease in the adsorption efficiency of the molecular sieve, which in turn makes the whitening phenomenon more serious, and the fluidity of the polyamide composite material is also reduced, making the surface rough and slightly floating fibers appear. It can be seen from the data of Comparative Example 3 and Comparative Example 3 that the addition of hyperbranched polyamide significantly improves the fluidity of the composite material and improves the appearance.
[0088] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0089] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a high-flowability polyamide composite material whose surface of automobile door frame trim does not turn white, characterized in that: The following steps are involved: A1, dispersing silicon source, aluminum source, organic template and alkali source in deionized water, mixing them evenly and placing them in a crystallization kettle for hydrothermal reaction to obtain a molecular sieve; A2, using an aminosilane coupling agent to graft-modify the surface of the molecular sieve to obtain an amino-modified molecular sieve; A3, putting the amino-modified molecular sieve and diethylenetriamine into a solvent, stirring evenly, adding succinic anhydride to react, and performing microwave digestion after the reaction to obtain a hyperbranched polyamide grafted modified molecular sieve; A4, adding polyamide resin, hyperbranched polyamide, hyperbranched polyamide grafted modified molecular sieve and additives to a high-speed blender for premixing to obtain a premix; feeding the premix into a twin-screw extruder from a main feeding port, feeding the glass fiber into the twin-screw extruder from a side feeding port, and melt-extruding and granulating to obtain; In step A2, the aminosilane coupling agent is at least one of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltriethoxysilane and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane.
2. The method for preparing a high-fluidity polyamide composite material with a non-whitening surface of an automobile door frame trim according to claim 1, characterized in that: In the step A1, the temperature of the hydrothermal reaction is 170-240° C. and the time is 26-72 hours.
3. The method for preparing a high-fluidity polyamide composite material with a non-whitening surface of an automobile door frame trim according to claim 1, characterized in that: In the step A1, the mass ratio of the silicon source, the aluminum source, the organic template and the alkali source is (5-5.3): (0.3-0.7): (2.1-4.3): (0.25-0.65).
4. The method for preparing a high-fluidity polyamide composite material with a non-whitening surface of an automobile door frame trim according to claim 1, characterized in that: In the step A2, the temperature during the grafting modification process is 70-90° C. and the time is 12-24 hours.
5. The method for preparing a high-fluidity polyamide composite material with a non-whitening surface of an automobile door frame trim according to claim 1, characterized in that: In the step A3, the usage ratio of the amino-modified molecular sieve, diethylenetriamine, succinic anhydride and solvent is (2-2.5): (3.3-3.7): (10.6-12.3): (170-200) mL.
6. The method for preparing a high-fluidity polyamide composite material with a non-whitening surface of an automobile door frame trim according to claim 1, characterized in that: In the step A3, the reaction temperature is 120-130° C. and the reaction time is 7-9 h.
7. The method for preparing a high-fluidity polyamide composite material with a non-whitening surface of an automobile door frame trim according to claim 1, characterized in that: In step A3, the microwave digestion treatment temperature is 130-180° C. and the time is 22-28 min.
8. The method for preparing a high-fluidity polyamide composite material with a non-whitening surface of an automobile door frame trim according to claim 1, characterized in that: In the step A4, the mass ratio of polyamide resin, glass fiber, hyperbranched polyamide, hyperbranched polyamide grafted modified molecular sieve and auxiliary agent is (55-70): (20-30): (1-3): (0.5-3): (0.1-4).
9. The method for preparing a high-fluidity polyamide composite material with a non-whitening surface of an automobile door frame trim according to claim 1, characterized in that: In step A4, the temperature of the twin-screw extruder is 245-280° C., and the screw speed is 250-400 rpm.
Citation Information
Patent Citations
Amino-terminated silicon oil modified amino-terminated hyperbranched polyamide resin and preparation method and application of polyamide resin
CN103073718A
Hyperbranched polyamidoamine and dendritic polyamidoamine composite flocculation decolorizing agent and preparation method and application thereof
CN103523885A